Unveiling Soil Fertility Dynamics in Rawalpindi Region: Implications for Sustainable Agriculture and Fertilizer Strategies (Journal of Agriculture and Veterinary Science, 2024)
In Pakistan, the adoption of high-yielding crop varieties and intensive farming practices since the commencement of the green revolution has led to a degradation in soil quality and fertility. Particularly in rainfed areas, rapid mineralization of soil organic matter (SOM) has exacerbated widespread nutrient deficiencies. This study, conducted in Rawalpindi district, aimed to evaluate the extent of soil nutrient deficiencies to formulate precise fertilizer recommendations for management of soil health and fertility to obtain sustainable crop production. A comprehensive analysis of 4080 soil samples from various tehsils within Rawalpindi district was carried out. Results revealed that the majority of soils (79%) were classified as loam, with an overwhelming percentage (88%) exhibiting alkaline pH (7.5 to 8.5). Furthermore, 99% of soils had an electrical conductivity (EC) within the safe limit of <4.00 dS m−1. However, more than 96% of soils displayed poor levels of SOM, and deficiency of available phosphorus was observed in 99% of the samples. Conversely, 63% of soils had adequate extractable potassium. These findings underscore that deficiency of SOM, available-P, and alkaline soil pH are the major contributing factors in Rawalpindi region to the poor soil fertility. Therefore, soil fertility management strategies must consider the findings of this study to obtain the maximum agronomic benefits. Furthermore, farmers are recommended to get their soil tested after every three years to revise the nutrient management programs.